Why Financial Knowledge Is Not Enough Behavioral Manipulation and Investment Scam Vulnerability in the Digital Age - Anuar, Amirul Ammar (Journal of Techno-Social, 2026)
Investment scams have become increasingly sophisticated in the digital age, targeting not only inexperienced investors but also educated and financially cautious individuals. While financial literacy is widely promoted as a key defense against fraud, growing evidence suggests that financial knowledge alone may be insufficient to protect individuals from increasingly sophisticated forms of deception. This study examines how investment understanding and behavioral manipulation interact to shape vulnerability to contemporary investment scams. This study employed a qualitative document research design using content analysis. A total of 42 publicly available regulatory reports, enforcement case summaries, and investor protection documents published by major international authorities between 2019 and 2024 were examined. The documents were systematically coded through open and axial coding procedures to identify recurring patterns of investor vulnerability and scammers’ persuasive strategies. The findings reveal two interrelated patterns. First, many victims demonstrated weaknesses in evaluating investment risks, verifying online credentials, and critically assessing promises of extraordinary returns. Second, scammers employed sophisticated behavioral tactics, including personalized communication, emotional engagement, fabricated identities, staged investment gains, and repeated requests for additional deposits to cultivate trust and reinforce commitment. These tactics often undermined rational judgment and influenced decision-making even among individuals possessing a basic level of financial knowledge. The findings suggest that investment scam vulnerability is driven not solely by deficiencies in financial knowledge but by the interaction between cognitive limitations and behavioral manipulation. This study contributes to the growing literature on financial fraud by highlighting the behavioral dimension of investor vulnerability and argues that effective investor protection requires the integration of financial literacy, behavioral awareness, and digital verification competencies within educational initiatives, regulatory interventions, and institutional safeguards.